Hybrid Language Teaching in Practice: Perceptions, Reactions, and Results - Carrasco, Berta (Springer, 2016)
This book allows readers to explore the inner workings of a hybrid class from the perspectives of two instructors with different pedagogical orientations, from the students’ perspectives, including learning outcomes and immediately practical teaching tools. The authors meet the challenge of how to preserve pedagogy and content while making good use of digital tools and online opportunities. Language teachers at the secondary and postsecondary level will enjoy the authors’ first person narrative of the creation of a pedagogically-sound hybrid course, practical examples from their courses, as well as student learning outcomes and feedback on the various technological activities. During a year-long study of the authors’ hybrid courses they used a mixed methods design to answers these questions: How does a hybrid course change our teaching? How does the hybrid course affect student learning experiences? What technology-based activities are most effective in our hybrid course?.